‘We have the solutions to our own problems’: supporting civil society in Nigeria (Overseas Development Institute, 2014)
Development assistance programmes that start from careful analysis of what works and what does not in country contexts are still remarkably rare. One reason for this is the lack of well documented examples of ‘ politically’ smart aid programming. To this end, this film outlines th e experience of the State Accountability and Voice Initiative (SAVI), a DFID-funded programme in Nigeria providing support to civil society, media and governmental organisations.